'How to raise a curtain': security, surveillance, and mobility in Canada's Cold War-era exchanges, 1955–65. Issue 2 (3rd April 2021) - Webb, Brandon
ABSTRACT: An extensive literature on the cultural Cold War has shown that winning the hearts and minds of rival populations distinguished the conflict as an ideological contest. Yet the question of how ideology influenced the tracking of cross-bloc travellers in cultural and scientific exchanges remains largely unexplored. This article examines Canada's ideological approach to screening and monitoring visitors from communist countries along with its covert interest in collecting foreign intelligence from visits to the Eastern bloc. By analysing declassified documents from Canada's security service, this article argues that transnational surveillance allowed the Canadian government to imprint its own vision of Cold War mobility.